Analisis Implementasi Kurikulum Merdeka di SMP IT Assalam Riau - Desi Novitasari; Evi Hasrina; Irfan Asyhari; Ichwanul Taufiq Nasution; Sri Andayani (ALSYS, 2026)
Although the implementation of the Kurikulum Merdeka has received attention in various studies, research specifically examining its implementation in the context of integrated Islamic schools, particularly at SMP IT Assalam Riau, remains limited. This study aims to analyze the implementation of the Kurikulum Merdeka at SMP IT Assalam Riau, covering the aspects of planning, implementation, and evaluation. This study used a qualitative approach with a case study design, involving informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation studies, and were then analyzed using thematic analysis techniques. The results showed that the implementation of the Kurikulum Merdeka was carried out through intracurricular learning, the Projek Penguatan Profil Pelajar Pancasila (P5), and extracurricular activities. The school demonstrated fairly good readiness through teacher training, learning communities, and foundation support. However, the implementation still faced obstacles in the form of limited technological facilities, teachers’ administrative workload, and the process of adapting to the new learning system. The conclusion of this study affirms that teacher readiness, institutional support from the school, and the integration of Islamic values are important factors in supporting the successful implementation of the Kurikulum Merdeka in integrated Islamic schools. These findings contribute to the development of educational policy studies and broaden understanding of the implementation of the Kurikulum Merdeka in the context of integrated Islamic institutions, while also providing practical implications for educational institutions in optimizing curriculum planning, implementation, and evaluation.